Wilding of a post-industrial site provides a habitat refuge for an endangered woodland songbird, the British Willow Tit Poecile montanus kleinschmidti. Issue 3 (2nd July 2020) - Broughton, Richard K.; Parry, Wayne; Maziarz, Marta
ABSTRACT: Capsule: Post-industrial sites that have become wilded by colonizing vegetation can represent important habitat refuges for Willow Tits Poecile montanus, which occupy large territories in early-successional wet woodland and scrub. Aims: To quantify Willow Tit population density and territory characteristics on a habitat mosaic of wetland, grassland and woodland/scrub, which has developed on a 596 ha area of former coal mining activities in northwest England. Methods: Field surveys located all 35–37 nests per year during 2017–2019. Territories were estimated using Thiessen polygons around nest sites. Remote sensing data (land cover mapping and lidar) characterized woody vegetation height and coverage across the site and within territories. Changes in coverage between 1990 and 2015 were assessed to estimate the age of woody vegetation. The relationship between territory size and woodland was tested to see if birds secure a similar area and volume of woody vegetation in each territory. Results: Mean breeding density was 7.3 pairs/km 2 (excluding 103 ha of ponds/lakes). Estimated territories averaged 13.7 ha, or 6.9 ha in wooded habitat only. The woodland and scrub were a maximum of 25–30 years old and had a mean height of 3.7 m. Larger territories contained a greater coverage and volume of wooded habitat. The site held 1.3% of the national and global population of the British subspecies of Willow Tit. Conclusion: Willow Tits occur at low density and require large areas of habitat. Wilded post-industrial sites appear to be important for Willow Tit conservation in Britain, but may require ongoing management to maintain the early-successional woodland and scrub associated with new wetlands in former mining areas. Such sites may have a broader conservation value for a range of species.